Analisis Forecasting Peserta KB Jenis Suntik dan Pil Di Kabupaten Sidenreng Rappang Dengan Metode Seasonal Autoregressive Moving Average (SARIMA) - Ahmad Faiz; Andi Mariani; Wahidah Alwi (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2024)
This study aims to analyze the increasing demand for contraceptives, making forecasting necessary to anticipate future needs and prevent supply shortages. To support this program, an effective forecasting method is required to predict the number of family planning (FP) participants in the future. This study employs the SARIMA (Seasonal Autoregressive Integrated Moving Average) time series method to forecast the number of FP participants using injections and pills in Sidenreng Rappang Regency. The results show that the SARIMA (0,1,0)(0,1,1)12 model is the most suitable for injection-based FP participants, while the SARIMA (1,1,0)(0,1,1)12 model is used for pill-based FP participants. The forecast indicates a decline in the numiber of injection and pill FP participants from January 2024 to December 2025.